Segmentation, Targeting, Positioning Strategy at PT. Kumala Motor Sejahtera Abadi Kendari (Case Study on The Hino Brand) - Indalestari, Wa Ode Dien; Lajaria , Ridha Taurisma; Zainuddin , Muh. Zabir; Manan , La Ode Abdul; Farih , Muhamad; Luki , Yongki (International Journal of Management and Education in Human Development, 2023)
This study aims to determine the Strategy for Implementing Segmentation, Targeting, Positioning at PT. Kumala Motor Sejahtera Abadi Kendari (Case Study on the Hino Brand). Data for analysis needs were obtained from interviews, observation, and documentation. Interviews were conducted with the leadership and employees of PT. Kumala Motor Sejahtera Abadi Kendari, and this the researchers used as informants in this study. The results showed that the application of segmentation carried out by PT. Kumala Motor Sejahtera Abadi Kendari uses several bases, including demographic segmentation with regard to age, gender and income as well as behavioral segmentation where this segment is more directed at the response of consumers or buyers whether they are happy or not with Hino products. The application of targeting determines the strategy for selecting the target market or target market using a Concentrated Targeting strategy where this strategy only focuses its marketing efforts on one group of buyers, namely consumers with middle to upper economic levels such as mining entrepreneurs and construction industry contractors. In the application of positioning, there are two, namely positioning according to price and quality where the price offered is higher but the quality offered is number one.